2018
DOI: 10.3329/bjsir.v53i2.36674
|View full text |Cite
|
Sign up to set email alerts
|

In vitro regeneration protocol of Rauvolfia serpentina L.

Abstract: An efficient in vitro regeneration system was developed for Rauvolfia serpentina L. through direct and indirect organogenesis from nodal and leaf explants. Among the different growth regulators, MS medium supplemented with 2.0 mg/l BAP, 0.5mg/l IAA and 0.02mg/l NAA found best for the multiple shoot formation from nodal segments. In this combination 98% explants produced multiple shoots and the average number of shoots per explants is 13∙4. The frequency of callus induction and multiple shoot induction from lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…1). Khan et al (2018) also found shoot regeneration on MS with BAP and IAA using leaf explants in Rawolfia. George and Rao (1980) also observed maximum regeneration from cotyledon explants in B. juncea with combinations of BAP.…”
Section: Resultsmentioning
confidence: 85%
“…1). Khan et al (2018) also found shoot regeneration on MS with BAP and IAA using leaf explants in Rawolfia. George and Rao (1980) also observed maximum regeneration from cotyledon explants in B. juncea with combinations of BAP.…”
Section: Resultsmentioning
confidence: 85%
“…Banu et al (2017) also observed better response in Gynura procumbens on MS with BAP, Kn and IAA supplemented medium. Khan et al (2018) also reported that combination of 2.0 mg/l BAP, 0.5 mg/l IAA and 0.02 mg/l NAA was best for the multiple shoot formation from nodal segments in Rauvolfia serpentina. Bhat et al (1995) showed that BA alone was more effective than Kn for different Piper spp.…”
Section: Resultsmentioning
confidence: 91%
“…Rani et al [1] reported axillary shoots of R. serpentina exhibited regeneration of maximum number of shoots on MS medium containing IAA and BAP. In another micropropagation study conducted by Khan et al [19] on R. serpentina, MS + BAP + NAA was found to be effective enough to induce direct regeneration of shoots from nodal segments and development of callus, followed by shoot regeneration from in vitro cultured leaf segments. In their study, regeneration from nodal and leaf segments was also achieved on MS + BAP + Kn and MS + BAP + IAA.…”
Section: Micropropagation and Phytochemical Analysis Of Rauvolfia Sermentioning
confidence: 93%